Corporate Environmental Responsibility: Capitalism, Legitimacy, and Ecological Harm Through the Lens of Green Criminology (Issues in Social and Environmental Accounting (ISEA), 2026)
This paper explores Corporate Environmental Responsibility (CER) through the lens of green criminology, offering a novel perspective on how capitalist-driven industrial activities contribute to environmental degradation. Integrating insights from the Treadmill of Production (ToP) and Legitimacy theories, it argues that the relentless pursuit of profit accelerates ecological harm through resource extraction (ecological withdrawal) and pollution (ecological addition). These activities heighten global sustainability challenges, including climate change, biodiversity loss, and resource scarcity. Companies increasingly adopt CER practices not merely as voluntary environmental stewardship but as a strategic response to legitimacy risks arising from these ecological impacts. By positioning themselves as environmentally responsible, organizations aim to maintain public trust, reduce regulatory scrutiny, and align with stakeholder expectations. This paper contributes to the literature by offering a theoretical understanding of CER's origin, situating it within broader global environmental concerns, and emphasizing CER's role in mitigating ecological and reputational risks in energy-intensive sectors.